Association between HLA-DQB1, -DPB1 alleles and risk of carbamazepine-induced hypersensitivity reactions in Vietnamese patients with epilepsy - Thi Thanh Nhan Le; Thi Tu Linh Nguyen; Lan Phuong Le; Doan Thuy Nguyen; Van Lieu Nguyen; Thi Van Anh Nguyen; Hong Thai Trinh (Vietnam Journal of Science, Technology and Engineering, 2024)
Adverse drug reactions are a serious problem for health and one of the main reasons for treatment failure with antiepileptic drugs. In this study, we determined the HLA-DQB1 and -DPB1 alleles in the blood samples of 44 epileptic patients receiving carbamazepine treatment, including 21 patients with hypersensitivity and 23 patients with tolerance, using the next-generation sequencing method. We identified 19 HLA-DQB1 alleles, of which 13 were in the hypersensitive group and 15 were in the tolerant group. The frequency of the HLA-DQB1*03:01:01 allele was highest in both groups. Although the frequency of the HLA-DQB1*03:03:02 allele in the hypersensitive group was higher than that in the tolerant group (p=0.0431), this difference was not statistically significant after applying the Bonferroni correction (pc=0.5249). However, the evidence of in silico interaction between CBZ and HLA- DQB1*03:03 at the peptide-binding cleft was suggested. For HLA-DPB1, 16 alleles were found in epileptic patients, with the HLA-DPB1*05:01:01 allele having the highest frequency; however, no allele was associated with the risk of hypersensitivity to carbamazepine in epileptic patients. Our study demonstrates that the HLA-DQB1*03:03:02 allele tended to behave as a susceptibility factor for carbamazepine-induced hypersensitivity reactions in Vietnamese patients with epilepsy.